2017
DOI: 10.3892/mmr.2017.6182
|View full text |Cite
|
Sign up to set email alerts
|

Sclareolide enhances gemcitabine-induced cell death through mediating the NICD and Gli1 pathways in gemcitabine-resistant human pancreatic cancer

Abstract: Pancreatic cancer is a type of cancer, which rapidly develops resistance to chemotherapy. Gemcitabine is the treatment used clinically, however, gemcitabine resistance leads to limited efficacy and patient survival rates of only a few months following diagnosis. The aim of the present study was to investigate the mechanisms underlying gemcitabine resistance in pancreatic cancer and to select targeted agents combined with gemcitabine to promote the treatment of pancreatic cancer. Panc-1 and ASPC-1 human pancrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Additionally, these studies highlighted that the EMT was triggered by TWIST and ZEB-1 transcription factors. By inhibiting TWIST and ZEB-1 the cells had an increased hENT-1 expression and reversed EMT phenotype, increasing gemcitabine efficacy [96,97]. These interesting results suggest that reversing cellular mechanical changes, i.e., EMT, could at least in part contrast the phenomenon of gemcitabine resistance relying on hENT-1.…”
Section: Mechanobiologymentioning
confidence: 91%
“…Additionally, these studies highlighted that the EMT was triggered by TWIST and ZEB-1 transcription factors. By inhibiting TWIST and ZEB-1 the cells had an increased hENT-1 expression and reversed EMT phenotype, increasing gemcitabine efficacy [96,97]. These interesting results suggest that reversing cellular mechanical changes, i.e., EMT, could at least in part contrast the phenomenon of gemcitabine resistance relying on hENT-1.…”
Section: Mechanobiologymentioning
confidence: 91%
“…4,6 Also, there are studies that indicate natural products such as sclareolide and Piperlongumine which can enhance the sensitivity of pancreatic cancer to gemcitabine. 8,9 These observations provide a proof of concept for finding a better treatment option and a diagnostic approach in management and treatment of PDAC patients. The only biological agent authorized to the treatment of pancreatic cancer is erlotinib together with gemcitabine; however, it brings about a moderate advantage of survival in unselected patients.…”
mentioning
confidence: 79%
“…It was observed that the association induced cell death through apoptosis, the upregulated expression of hENT1, downregulated expression of RRM1 and inhibition of the EMT through the TWIST1/Slug pathway, which was mediated by NICD/Gli1. The authors proposed the combination as a potential strategy for the treatment of patients with gemcitabine-resistant pancreatic cancer [ 122 ].…”
Section: Other Bioactive Sesquiterpene Lactones Tested In Pdac Modelsmentioning
confidence: 99%